Comparative Study Of Vehicle Fuel Economy With And Without Engine Start-Stop Strategies - Ong, Horng Neng (Universiti Sains Malaysia, 2017)
The start-stop functionality is widely used as a fuel saving solution for on-highway vehicles, being constantly studied and implemented in new series models. The subject of this work is to demonstrate the same start-stop functionality applied for city road vehicles in Malaysia. The implementation of the start-stop system in a conventional car aims for a reduction on fuel consumption and prolong the fuel economy. The start-stop behavior is recorded by using OBD-II adapter through ECU. These interventions are important discussions topics and include fuel consumption study by using forward facing model developed. The data recorded via OBD-II is analyzed and used as input in the Simulink model. The result shows that the fuel economy can be boosted up to 1.412%. This indicates that vehicle with start – stop practice can travel further with same amount of petrol when comparing to conventional vehicle.